The Influence of Blue Economy on the Economic Growth of Sumenep Regency - Prasetyo, Alvin Sugeng; Wantara, Pribanus; Alfinuri, Nadila (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
This study is urgent because Sumenep Regency, located in the Madura archipelago, has a long coastline and access to abundant marine resources. However, the challenges faced are overfishing, marine pollution, and coral reef damage are serious threats. In addition, rising sea levels and changes in weather patterns can significantly impact the economy of coastal communities. The purpose of the research in this study is to test and analyze the influence of the blue economy on economic growth in Sumenep Regency. The method used is multiple regression for the period 2010 to 2023. The estimation results show that the variables of the fisheries sector, marine tourism, and environmental conservation positively impact the economic growth of Sumenep Regency. This research helps optimize regional potential and ensure that the development does not damage the ecosystem and continues to benefit future generations. Keywords: The Blue Economy, Economic Growth, Multiple Regression